2009
DOI: 10.1111/j.1472-765x.2008.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromogenic media for the isolation of vancomycin-resistant enterococci from stool samples

Abstract: Aims:  This study sought to evaluate the performance of two chromogenic media designed for the isolation of vancomycin‐resistant enterococci (VRE) and compare them with a traditional bile‐esculin medium for the isolation of VRE from stool samples. Methods and Results:  A total of 285 stool samples were inoculated onto Chromogenic VRE Agar (AES VRE agar; AES Chemunex), chromID VRE (bioMérieux) and VRE Agar (Oxoid) both directly and also following broth enrichment. In total 18 strains of vancomycin‐resistant Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…All studies reported similar rates of recovery of both VRENFM and VRENFS from chromogenic agars to those from BEAV (1,2,(4)(5)(6)(7)10). CVRE appeared to perform better than the other chromogenic agars compared to BEAV, but a direct comparison is needed to provide the most accurate comparison.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…All studies reported similar rates of recovery of both VRENFM and VRENFS from chromogenic agars to those from BEAV (1,2,(4)(5)(6)(7)10). CVRE appeared to perform better than the other chromogenic agars compared to BEAV, but a direct comparison is needed to provide the most accurate comparison.…”
mentioning
confidence: 88%
“…Confirmation of VRE using this medium requires 48 to 72 h. Chromogenic agars to detect VRE demonstrate promise (1)(2)(3)(4)(5)(6)(7)10). BBL CHROMagar VanRE (CVRE; BD Diagnostics, Sparks, MD) is a selective and differential chromogenic agar under development for the detection of vancomycin-resistant E. faecium (VRENFM) and vancomycin-resistant Enterococcus faecalis (VRENFS).…”
mentioning
confidence: 99%
“…Various chromogenic VRE agars appear promising for use in VRE stool screening (1,3,(4)(5)(6)11). Chromogenic VRE media can reduce turnaround time to results through early visual colony identification.…”
mentioning
confidence: 99%
“…Several formulations of chromogenic media have been developed to shorten this turnaround time and they are supposed to be used with or without enrichment step. Although many investigators reported that various chromogenic VRE agars appeared promising for use in VRE stool screening [3][4][5][6][7][8], only a few studies compared them with the method including the enrichment step [6].…”
Section: Introductionmentioning
confidence: 99%